Human Mesenchymal Stromal Cell-Mediated Immunoregulation: Mechanisms of Action and Clinical Applications. (29th September 2013) - Dorronsoro, Akaitz; Fernández-Rueda, Jon; Fechter, Karoline; Ferrin, Izaskun; Salcedo, Juan Manuel; Jakobsson, Emma; Trigueros, César
Abstract : Mesenchymal stromal cells (MSCs) are multipotent cells found in connective tissues that can differentiate into bone, cartilage, and adipose tissue. Interestingly, they can regulate immune responses in a paracrine way and allogeneic MSCs do not elicit immune response. These properties have encouraged a number of clinical trials in a broad range of regenerative therapies. Although these trials were first focused on their differentiation properties, in the last years, the immunosuppressive features have gained most of the attention. In this review, we will summarize the up-to-date knowledge about the immunosuppressive mechanisms of MSCs in vivo and in vitro and the most promising approaches in clinical investigation.